In situ study of aggregate topology during growth of pyrolytic silica. (April 2018) - Rai, Durgesh K.; Beaucage, Gregory; Vogtt, Karsten; Ilavsky, Jan; Kammler, Hendrik K.
Abstract: Ramified aggregates are formed in many kinetically-limited growth processes such as in sooting flames. The structures are disordered and present a challenge to quantification. The topology of such nanomaterials is important in understanding their formation and properties. Recently, a method has been developed for the quantification of branching in aggregates using small-angle scattering. The method allows for determination of the average number of branches, branch length, short circuit path through an aggregate, aggregate total mass, aggregate polydispersity, primary particle coordination number, Sauter mean diameter, primary particle polydispersity, particle size distribution, and surface to volume ratio. In this report the new topological method is applied to in situ measurements previously published from a flame aerosol as a function of height above the burner. The topological evolution of primary and fractal structures is observed. This facilitates the understanding of growth dynamics and the structural rearrangements that occur during flame synthesis. Highlights: Branching in silica aggregates is quantified using in situ x-ray scattering from a premixed flame. Aggregategrowth follows three stages: 1) initial nucleation and rapid growth; 2)coalescence; and 3) agglomeration of aggregates. Average number and length of branches, and branch-on-branch or hyperbranch content are determined. The number and volume fraction of silica, as well as other structural parameters agree with a previous study on this flame. Graphical abstract: